2015
DOI: 10.1037/sgd0000117
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and collective action: Exploring buffers against minority stress for transgender individuals.

Abstract: With a national sample of 552 transgender adults, the present study tested hypotheses drawn from minority stress theory and positive psychology research on stress-ameliorating processes. Specifically, the present study examined the relations of minority stressors (i.e., antitransgender discrimination, stigma awareness, and internalized transphobia) and individual-and group-level buffers (i.e., resilience and collective action) of minority stress. As expected, each minority stressor was positively correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
198
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(223 citation statements)
references
References 82 publications
(167 reference statements)
19
198
2
4
Order By: Relevance
“…Increased social support and self‐esteem also bolstered resilience. Resilience has been shown to protect against psychological distress in the face of minority stressors (Breslow et al, ), and as identified in this study, may promote positive mental and behavioral health. This body of work along with the present findings highlight the importance of a positive support system from family, friends, and significant others to foster a sense of pride, self‐worth, resilience, and positive mental and physical health.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Increased social support and self‐esteem also bolstered resilience. Resilience has been shown to protect against psychological distress in the face of minority stressors (Breslow et al, ), and as identified in this study, may promote positive mental and behavioral health. This body of work along with the present findings highlight the importance of a positive support system from family, friends, and significant others to foster a sense of pride, self‐worth, resilience, and positive mental and physical health.…”
Section: Discussionmentioning
confidence: 68%
“…Increased social support and self-esteem also bolstered resilience. Resilience has been shown to protect against psychological distress in the face of minority stressors (Breslow et al, 2015), and as identified in this study, may promote positive mental and behavioral health.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…32 Additional stressors include perceived transgender stigma, 33,34 internalized transphobia, 34,35 gender-related rejection and victimization, 31 nonaffirmation of gender identity, 27,36 and nondisclosure of transgender identity. 34 …”
Section: Minority Stress Modelmentioning
confidence: 99%